Idionyx pseudovictor sp. nov. from Fujian, China (Odonata: Anisoptera: Corduliidae) - Xu, Qi-Han (Zootaxa, 2013)
A new species of the genus Idionyx Hagen, I. pseudovictor sp. nov. from Fujian, China is described from the female, il-lustrated and diagnosed from its congeners. Description of the final stadium larva of the new species is also provided. The new species is closely similar to female I. victor. There are a series of relatively minor colour and pattern differences be-tween these two female adults, as well as a series of obvious structural differences in larvae of these two species. The fe-male adult of the new species can be separated from that of I. victor by the following characters: (1) labrum entirely yellow; (2) distal end of ventral synthorax entirely yellow; (3) abdominal S1–2 with complete middorsal yellow stripe; (4) valvula vulvae pointed triangularly, not projecting beyond apical border of 8th tergite. The larva of the new species can be separated from that of I. victor by the following characters: (1) body dark brown, covered with dense long hairs; (2) apical border of prementum with 10 spiniform setae on each side; (3) premental setae 5+3/5+3; (4) numerous fine bristles present on median lobe; (5) inner margin of palpal lobe with 6 large projections; and (6) movable hook long and acuminate.